70.5k views
4 votes
4(b-1)= -4+4b what is the solution

1 Answer

3 votes

Starting with the equation:


4(b-1)=-4+4b

Use the distributive property to expand the parenthesis in the left hand side of the equation:


4b-4=-4+4b

Use the commutative property to rewrite the right hand side of the equation, swapping the terms:


4b-4=4b-4

Since both sides of the equation are the same, any value of b is a solution to the equation.

Therefore, all numbers are a solution for the equation 4(b-1)=-4+4b.

User Mohamed Rafiq P
by
5.0k points